2019
DOI: 10.1016/j.oret.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Nonsupine Positioning after Macular Hole Surgery

Abstract: To evaluate the postoperative closure rate of full-thickness macular holes (MH) after nonsupine positioning, which means that the patients avoid upward gaze and a supine sleeping position, and to investigate the correlation between postoperative positioning compliance and closure rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…In contrast, 13.1% of United States retina surgeons in the 2018 ASRS PAT survey reported that they do not position their patients face-down following macular hole surgery. [ 6 ] In a recent prospective multicenter study, Lindtjørn, et al [ 35 ] reported a 99.5% MH closure rate with 3–5 days of postoperative nonsupine (but not face-down) positioning. The authors suggest that their results corroborate those of others who have found strict face-down positioning to be unnecessary in achieving successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 13.1% of United States retina surgeons in the 2018 ASRS PAT survey reported that they do not position their patients face-down following macular hole surgery. [ 6 ] In a recent prospective multicenter study, Lindtjørn, et al [ 35 ] reported a 99.5% MH closure rate with 3–5 days of postoperative nonsupine (but not face-down) positioning. The authors suggest that their results corroborate those of others who have found strict face-down positioning to be unnecessary in achieving successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lindtjørn et al strongly proposed that non-supine positioning provided excellent closure of idiopathic macular holes. He also suggested that complete gasfoveal contact without minor interruptions was not necessary for macular hole closure 13 . Contrary to that another researcher suggested that degree of gas fill had considerable effect on the results of hole closure 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in rare cases, the face-down position can also cause systemic complications such as pulmonary embolism, thrombophlebitis, and ulnar nerve palsy [5][6][7] . To overcome these problems, recent studies have reported that a strict face-down position may not be necessary [8][9][10][11] . PPV with complete drainage of subretinal fluid (SRF) and no face-down positioning in the postoperative period leads to a high anatomical retinal reattachment rate in the primary pseudophakic RRD [4,[8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, recent studies have reported that a strict face-down position may not be necessary [8][9][10][11] . PPV with complete drainage of subretinal fluid (SRF) and no face-down positioning in the postoperative period leads to a high anatomical retinal reattachment rate in the primary pseudophakic RRD [4,[8][9] . Chen et al [10] reported that for RRD repair, the primary retinal reattachment rate of PPV with gas tamponade and a flexible postoperative position (alternative upright or lateral recumbent) was the same as that with a strict face-down position.…”
Section: Introductionmentioning
confidence: 99%